2021
DOI: 10.1007/s11207-021-01865-7
|View full text |Cite
|
Sign up to set email alerts
|

Can Multi-threaded Flux Tubes in Coronal Arcades Support a Magnetohydrodynamic Avalanche?

Abstract: Magnetohydrodynamic (MHD) instabilities allow energy to be released from stressed magnetic fields, commonly modelled in cylindrical flux tubes linking parallel planes, but, more recently, also in curved arcades containing flux tubes with both footpoints in the same photospheric plane. Uncurved cylindrical flux tubes containing multiple individual threads have been shown to be capable of sustaining an MHD avalanche, whereby a single unstable thread can destabilise many. We examine the properties of multi-thread… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Starting from a potential field, Reid et al ( 2018 ) introduce a model that self-consistently produces an MHD avalanche, with the generation of significant heating. Moving from a straightened model, with flux tubes connecting two parallel planes (in the style treated by Parker 1972 ), to a curved potential field, Threlfall, Reid & Hood ( 2021 ) extend this, confirming the viability of avalanches in the new, curved geometry. Here, that work is extended.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Starting from a potential field, Reid et al ( 2018 ) introduce a model that self-consistently produces an MHD avalanche, with the generation of significant heating. Moving from a straightened model, with flux tubes connecting two parallel planes (in the style treated by Parker 1972 ), to a curved potential field, Threlfall, Reid & Hood ( 2021 ) extend this, confirming the viability of avalanches in the new, curved geometry. Here, that work is extended.…”
mentioning
confidence: 64%
“…Volume-integrated magnetic, kinetic, and internal energies evolve in the manner outlined in Threlfall et al ( 2021 ), and as demonstrated by their respective evolutions o v er time in Fig. 2 .…”
Section: Energiesmentioning
confidence: 80%
See 3 more Smart Citations